Understanding multiple sclerosis - Stauffer, Melissa (Understanding health and sickness series., 2006)
Annotation Two-and-a-half million people world-wide and 400,000 Americans suffer from the chronic disease multiple sclerosis. Understanding Multiple Sclerosis presents both general information about MS and valuable, specific advice. Who gets MS? What are its symptoms? What are its effects on the bodies and minds of people afflicted? How does one plan for the future after a diagnosis? From basic biology to new advances in treatment, Understanding Multiple Sclerosis covers the topics most relevant to people with MS and to their families and friends. Chapters provide:Introduction to genetic, demographic, and geographic factorsBasic biology of MS, with descriptions of both the central nervous system and the immune systemCharacteristic symptoms of MSDiagnostic criteria and different types of MSTreatments, over-the-counter medica-tions, and alternative medicinesLifestyle adjustments and coping strate-gies along with advice on long-term health insurance and financial planningCurrent and ongoing MS research and advancesMelissa Stauffer of Daphne, Alabama, is a freelance science editor whose work has appeared inBiochemistry, Journal of Biological Chemistry, Journal of Biomolecular NMR, andFEBS Letters.